Concept Development of Automatic Sliding Door and Light Using NodeMCU Sensor - Pandini, Jasmine; bin Zulkipli, Muhammad Asyrad; Fenoria Putri (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The rapid advancement of technology has led to the emergence of smart systems that aim to enhance convenience, energy efficiency, and safety. In this study, we present the development of an automatic door and light system utilizing a NodeMCU sensor. The system is designed to automatically control open and close the door, as well as lighting in indoor environments. To implement the system, this experiment utilized the NodeMCU sensors onboard Wi-Fi capabilities, enabling remote control and monitoring via a dedicated mobile application. The application provides users with the ability to customize various system parameters, according to their specific requirements. This development offers a practical and connected solution to automate door and light, increasing safety, comfort and energy efficiency in premise, house or any buildings. It can enable users to control both the door and light remotely, providing convenience and flexibility. This automatic sliding door and light can unlock the system by sending commands through the Blynk application on the user's smartphone, then NodeMCU sensor as a microcontroller will confirm the command and send data to other components to move sliding door and turn on the light, the use of this system is very effective because it makes it easier for users to open and close the door and turn on and turn off the light without extra efforts.